Development of Sustainable Light Weight Foamed Concrete Based On Construction and Demolition Debris - Anil; Dr. Varinder Singh; Er. Rajbala (International Journal of Scientific Research in Civil Engineering, 2025)
The construction industry’s growing demand for concrete contributes significantly to natural resource depletion and carbon emissions. In response, this study proposes sustainable lightweight foamed concrete (LFC) utilizing construction and demolition waste (CDW) as recycled aggregate. The research investigates how CDW granulometry (fine, medium, and coarse) and varying foam content influence the mechanical properties of LFC. Twelve mix designs were organized using a fixed water–cement ratio (0.64), and performance metrics such as compressive strength (CS), water absorption, air void content, and bulk density were assessed. ANOVA revealed foam content as the most significant factor influencing CS (71% contribution), followed by CDW granulometry (15%). Optimal compressive strength was observed at 3.8% foam content with coarse CDW, achieving a strength of approximately 4.5 MPa. The findings support the feasibility of incorporating CDW in LFC production, offering a sustainable alternative that reduces environmental impact while maintaining acceptable performance for non-structural applications.